2012
DOI: 10.1007/s00276-012-1010-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the mandibular divergence on the position of the inferior alveolar nerve and mylohyoid nerve: a computed tomography study and its relevance to bilateral sagittal split osteotomy

Abstract: The IAN seems to have a more superior position in the groups of mandibular hypo- and hyper-divergence. Orthognathic surgeons should use a more superficial retromolar bone incision in these cases. Finally, the Epker technique would be safer for preserving the MHN in normo- and hypo-divergent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
0
13
0
6
Order By: Relevance
“…A transient or permanent sensory deficit around the skin of the chin, without affecting the sensation of the lower lip [235], has been reported following removal of the submandibular gland, during which the gland is physically separated from the NM [2233536], a bilateral sagittal split osteotomy (BSSO) [4], and post-genioplasty [35].…”
Section: Injury To the Nm During Maxillofacial Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…A transient or permanent sensory deficit around the skin of the chin, without affecting the sensation of the lower lip [235], has been reported following removal of the submandibular gland, during which the gland is physically separated from the NM [2233536], a bilateral sagittal split osteotomy (BSSO) [4], and post-genioplasty [35].…”
Section: Injury To the Nm During Maxillofacial Surgerymentioning
confidence: 99%
“…The NM, then, courses in the mylohyoid groove (Figs. 1, 2) or canal situated on the medial aspect of the mandibular ramus [1234]. The nerve then gives off motor branches, which penetrate the inferior aspect of the mylohyoid muscle and the anterior belly of the digastric muscle [12345].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The MM and ADM, involved in mastication, deglutition, respiration and speech, are innervated by the MHN. 3,4 The nerve also carries the sensory information from other teeth. 5 Histological study 6 revealed that MHN contains fibres that might provide sensory innervation to the mesial root of the mandibular first molar, premolars, incisor teeth and the skin below the chin.…”
Section: Introductionmentioning
confidence: 99%